Optimization and Evaluation of Poly(lactide-co-glycolide) Nanoparticles for Enhanced Cellular Uptake and Efficacy of Paclitaxel in the Treatment of Head and Neck Cancer - Haider, Mohamed; Elsherbeny, Amr; Jagal, Jayalakshmi; Hubatová-Vacková, Anna; Saad Ahmed, Iman (Pharmaceutics, 2020)
The particle size (PS) and encapsulation efficiency (EE%) of drug-loaded nanoparticles (NPs) may inhibit their cellular uptake and lead to possible leakage of the drug into the systemic circulation at the tumor site. In this work, ultra-high paclitaxel-loaded poly(lactide-co-glycolide) NPs (PTX-PLGA-NPs) with ultra-small sizes were prepared and optimized by adopting the principles of quality by design (QbD) approach. The optimized PTX-PLGA-NPs showed ultra-small spherical particles of about 53 nm with EE% exceeding 90%, a relatively low polydispersity index (PDI) of 0.221, an effective surface charge of -10.1 mV, and a 10-fold increase in the in vitro drug release over 72 h relative to free drug. The cellular viability of pharynx carcinoma cells decreased by almost 50% in 24 h following treatment with optimized PTX-PLGA-NPs, compared to only 20% from the free drug. The intracellular uptake of PTX-PLGA-NPs was highly favored, and the antitumor activity of PTX was remarkably improved with a reduction in its half maximal inhibitory concentration (IC50), by almost 50% relative to free drug solution. These results suggest that the optimal critical formulation parameters, guided by QbD principles, could produce PLGA-NPs with remarkably high EE% and ultra-small PS, resulting in enhanced cellular uptake and efficacy of PTX.
Keywords: quality-by-design; head and neck cancer; nanoparticles; poly(lactide-co-glycolide); paclitaxel